The impact of leadership styles on the social responsibility of industrial companies in Romania - Mohammed, Raghad; Costea, Carmen Eugenia (Journal of Economic Development, Environment and People, 2023)
This study aimed to examine the impact of leadership styles on the social responsibility of industrial companies in Romani. To achieve this objectives the study used descriptive analytical approach through develop questionnaire to collect data from the sample which consists (357) managers who work in industrial companies in Romani. A total of (340) suitable questionnaire were retrieved for statistical analysis, the study used Statistical Package for the Social Sciences software (SPSS. 25) to analyses the collecting data and test the hypothesis. The study results showed that, there is impact of Authoritative leadership on social responsibility of industrial companies in Romania, there is impact of Democratic leadership on social responsibility of industrial companies in Romania, there is impact of Facilitative leadership on social responsibility of industrial companies in Romania, and there is no impact of Situational leadership on social responsibility of industrial companies in Romania. In light of these findings the study recommended the need to pay attention to the quality of leaders who are appointed in industrial companies in Romania due to the clear impact of the quality of leadership at the level of social responsibility practices of companies.